2016
DOI: 10.3168/jds.2015-10565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary sugar concentration and sunflower seed supplementation on lactation performance, ruminal fermentation, milk fatty acid profile, and blood metabolites of dairy cows

Abstract: Previous research has shown that both sunflower seed (SF) and sucrose (SC) supplementation can result in variation in milk fat concentration and composition, possibly due to altered fermentation patterns and biohydrogenation of fatty acids in the rumen. The objective of this study was to determine the effects of different sugar concentrations with or without SF supplementation on lactation performance, ruminal fermentation, and milk fatty acid profile in lactating dairy cows. Eight multiparous Holstein dairy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In the present experiment, total VFA concentration in the rumen was not altered by LM inclusion, which agrees with previous studies (Penner and Oba, 2009;Razzaghi et al, 2016). Cows fed the BFM-supplemented diets showed a trend for increased total VFA concentration in the rumen.…”
Section: Ruminal Vfa and Lactatesupporting
confidence: 93%
See 3 more Smart Citations
“…In the present experiment, total VFA concentration in the rumen was not altered by LM inclusion, which agrees with previous studies (Penner and Oba, 2009;Razzaghi et al, 2016). Cows fed the BFM-supplemented diets showed a trend for increased total VFA concentration in the rumen.…”
Section: Ruminal Vfa and Lactatesupporting
confidence: 93%
“…The effects of dietary inclusion of sugars via sucrose or molasses (dried or liquid) on DMI have been inconclusive across the literature. Previous studies conducted with lactating dairy cows reported no effect of sources rich in disaccharides on DMI either in typical (Razzaghi et al, 2016) or high-concentrate diets (Martel et al, 2011), whereas others (Broderick et al, 2008;Penner and Oba, 2009) observed increased DMI. A possible explanation for the positive effect of LM on DMI could be related to improved diet palatability (Khalili and Huhtanen, 1991).…”
Section: Intake and Milk Yield And Compositionmentioning
confidence: 86%
See 2 more Smart Citations
“…The higher ethanol soluble carbohydrate concentration in the sorghum silage versus corn silage in the current study may have contributed to the increased milk fat, although the increase in sugar was only around 0.25% of the diet DM due to the sorghum silage, so the effect may have been small. Razzaghi et al (2016) reported higher fat content and lower total milk trans-18:1 FA with a sucrose treatment. It is known that increases in trans-10 18:1 milk FA are positively related to milk fat depression for cows fed a low-fiber, high-oil diet (Rico and Harvatine, 2013).…”
Section: Resultsmentioning
confidence: 90%